Assistance provided to people with non-suicidal self-injuries: creation and validation of a simulated scenario - Ramos, Aline Mendonça; Silva, Aline Conceição; Pedrollo, Laysa Fernanda Silva; Vedana, Kelly Graziani Giacchero (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2023)
Objective: to create and validate a simulated scenario for health assistance to people withnon-suicidal self-injuries. Methodology: a methodological study for creating and validating ahigh-fidelity simulated scenario. A script based on good practices in high-fidelity simulation andnon-suicidal self-injuries subsidized creation of the scenario. Validation was in charge of elevenspecialists. We assessed the simulated scenario with a three-point Likert scale (Good, Fair andPoor). We analyzed the data using a statistical software program and employed descriptiveanalysis, the Content Validity Index and the Gwet test. Results: the scenario obtained 97%overall agreement among the specialist judges and all individual items had Content Validity Indexvalues over 0.80. The scenario presented high total reliability (Gwet test: 0.9438) and reliabilityon both topics of interest in the Gwet test. Conclusion: the non-suicidal self-injury simulatedscenario developed has the potential to collaborate with the training of human resources inhealth for assisting people with non-suicidal self-injuries.